K. S. Singh. An anthropological Atlas. Ecology and Cultural Traits, Languages and Linguistic Traits, Demographic and Biological Traits. Delhi: Anthropological Survey of India, Oxford University Press, 1993. People of India National Series, vol. XI. - Dube, Saurabh (Estudios de Asia y África, 1997)
-